Formulation and Evaluation of Sustained and Raft Forming Antacid Tablet - Mohammed S. Al-Lami (College of Pharmacy University of Baghdad, 2017)
Antacids have been widely used in the treatment of various gastric and duodenal disorders such as heartburn, reflux esophagitis, gastritis, irritable stomach, gastric and duodenal ulcers. A pH-responsive of bi-polymer of sodium alginate and pectin have been studied as raft-forming polymers using sodium bicarbonate and calcium carbonate as gas-generating and calcium ion sources. The aim of study was to formulate and evaluate mono and bilayer tablets of floating and sustained release antacid delivery systems using sodium carboxy methyl cellulose as a gel forming substance, calcium and magnesium carbonate as sources of acid neutralizing and carbon dioxide gas generators agents upon contact with acidic solution. The effect of the formulation contents on the buoyancy has been investigated. In addition to, the antacid activities of intact and pulverized tablets have been studied. The result obtained showed that the buoyance is remarkably affected by the percentages of sodium carboxy methyl cellulose and carbonates salts. All formulas of mono and bilayer tablets revealed sustained action of acid neutralization and raft formation. Besides, bilayer tablets showed a significant and higher level of acid neutralizing capacity than monolayer tablets. Moreover, the pulverized of bilayer tablets exhibited significant and higher acid neutralizing capacity at raft than that at bulk of artificial gastric juice medium. Keywords: Raft forming agent, Antacid, floating drug delivery, Acid neutralizing capacity, Sodium carboxy methyl cellulose.